Efektivitas Dan Dampak Program Dana Penguatan Modal Lembaga Usaha Ekonomi Pedesaan (DPM-LUEP) Terhadap Pendapatan Dan Kesempatan Kerja Petani Padi Di Kabupaten Tabanan - Darawati, Ni Made Dwi; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Indonesian population growth is fast resulting in growing demand for rice. Annual production of commodity grain/rice harvest time showing very abundant production, but demand each month grain/rice is relatively stable, which makes the price of grain/rice down. In order to increase the price of farmer’s grain and to maintain the price stability concurrently with decreasing poverty in rural area, the government established the Capital Reinforcement Fund Aid Program of Rural Economy Business Organization (DPM-LUEP). This Capital Reinforcement Fund Aid Program of Rural Economy Business Organization (DPM-LUEP) is a facility providing business capital assistance which mostly will be used as additional business capital for rice milling business on the aim to buy the farmer’s grain accordingly to Government Purchase Price (HPP). The aim of this study to scale the effectiveness level and the impact of DPM-LUEP aid program to income and job opportunity the farmer’s in Tabanan Regency. Samples in this study amounted to 58 respondents. Research methods used is statistic descriptive to understand the effectivity of program and also statistic analysis of the average difference test of paired observation (t-test) to understand the impact of Capital Reinforcement Fund Aid Program of Rural Economy Business Organization (DPM-LUEP) to job opportunity and income the farmer’s in Tabanan Regency. Analytic result showed that the effectivity level of Aid Program DPM-LUEP is 90,5 percent which means Capital Reinforcement Fund Aid Program of Rural Economy Business Organization is very effective. The result also showed that Aid Program DPM-LUEP positively impact to the increase of income and increase the farmer’s opportunity in Tabanan Regency.